To the Ones I Call Home - Putri, Vinanda Cinta Cendekia (2025)
Some moments of life are worth more than to let them get away. Soft, brief, but unreplaceable. Instead of enclosing them in pictures, the author has chosen to preserve them in words.It is not a poetry book; it's a loving photo album of memory filled with love and living. By poetic vignettes, the author tells us about family. A faithful husband, a kind firstborn, and a rambunctious second child.Every poem captures the special beat of their lives, infusing love, growth, and unity. This book is a love letter, a testament that preserving precious memories through the beauty of poetry.